Galactic Magnetic Fields. II. Applying the Model to Nearby Galaxies - Rion Glenn Nazareth; Gayathri Santhosh; Luke Chamandy (The Astrophysical Journal)
Many spiral galaxies host magnetic fields with energy densities comparable to those of the turbulent and thermal motions of their interstellar gas. However, quantitative comparison between magnetic field properties inferred from observation and those obtained from theoretical modeling has been lacking. In L. Chamandy et al. (Paper I ), we developed a simple, axisymmetric galactic dynamo model that uses various observational data as input. Here, we apply our model to calculate radial profiles of azimuthally and vertically averaged magnetic field strength and pitch angle, gas velocity dispersion and scale height, turbulent correlation time and length, and the sizes of supernova remnants for the galaxies M31, M33, M51, and NGC 6946, using input data collected from the literature. Scaling factors are introduced to account for a lack of precision in both theory and observation. Despite the simplicity of our model, its outputs agree fairly well with galaxy properties inferred from observation. Additionally, we find that most of the parameter values are similar between galaxies. We extend the model to predict the magnetic field pitch angles arising from a combination of mean-field dynamo action and the winding up of the random small-scale field owing to the large-scale radial shear. We find their magnitudes to be much smaller than those of the pitch angles measured in polarized radio and far-infrared emission. This suggests that effects not included in our model, such as effects associated with spiral arms, are needed to explain the pitch angle values.